ENFORCEMENT OF CRIMINAL LAWS AGAINST USERS AND PROVIDERS OF PROSTITUTION SERVICES IS SEEN FROM SEVERAL STATE COURT RULING - Aldri; Ediwarman; Mahmud Mulyadi (Journal of International Islamic Law, Human Right and Public Policy, 2024)
Prostitution or prostitution is one of the many disgraceful acts. This act is considered to be contrary to the values ​​that grow in society because it is not in line with religious provisions and community customs. The research method used in this research is normative legal research. Normative legal research is legal research that uses secondary data sources. The results of this research are: there are no regulations governing the crime of prostitution in Indonesia, the factors that influence users and providers of prostitution services can come from themselves or the influence of the environment and criminal law policies regarding criminal liability for providers and users of prostitution services. It should be reformulated because it is not in accordance with society's values ​​and can have negative effects on health.